THE INTERGROUP EXPRESSION OF ETHNOCENTRISM PORTRAYED BY WIZARD IN FANTASTIC BEASTS TRILOGY - Maslahatul Hanis, Leny; Murtiningrum, Afina (Universitas Duta Bangsa Surakarta, 2025)
Ethnocentrism refers to a social phenomenon in which an individual or group believes that they are superior in various aspects, including culture, tradition, spiritual and strength, while disregarding or demeaning other groups. Social issues can occur anywhere and can also be discussed and raised in any literary work. One of the literary works is a movie. Therefore, this study analyzes the intergroup expression of ethnocentrism portrayed by wizards in the Fantastic Beasts trilogy. The objective of this study is to identify the kind of expressions of ethnocentrism depicted and raised in the Fantastic Beasts trilogy. The phenomenon of prioritizing the interests of one's own ethnic group over those of other ethnic groups is clearly examined in the case of wizards and muggles. The qualitative approach that emphasizes the film script as the data source. This study uses the theories of Bezumic and Duckitt on expressions of ethnocentrism between groups. The result of this study is how wizards portray 2 of the 4 types of theoretical expressions of intergroup ethnocentrism towards muggles, which are superiority and purity.